Early mobilization in the Intensive Care Unit (Research, Society and Development, 2022)
Introduction: For a patient to maintain his quality in an Intensive Care Unit, it is necessary for him to be assisted by a multidisciplinary team that meets his basic, physiological and psychological needs. Patient care in the ICU aims to provide the necessary comfort, as well as seek maneuvers that can relieve the time that this individual is bedridden. Early mobilization is a therapeutic resource, where the physical therapist assists the patient, using exercises with the purpose of maintaining range of motion, muscle stretching and trophism, in addition to preventing the patient from suffering thromboembolism and functional decline, while he is in the intensive care unit, as well as after hospital discharge. Objective: To elucidate the importance of early mobilization in the Intensive Care Unit. Methods: Literature review on Early Mobilization in the Intensive Care Unit. The study was carried out through research in electronic, national and international databases in Portuguese and English, academic google and Scielo. Results: 40 articles were found, but after refinement, 21 articles were selected because they met the research inclusion criteria. Final Considerations: Early mobilization is effective for the rapid recovery of the patient, presents positive results, thus positively reducing the length of stay and minimizes the deleterious consequences of hospitalization, giving the patient an improvement in the quality of life after discharge from the ICU.